Idealist alternatives to materialist philosophies of science - MacEwen, Philip, (Religious Studies, Theology and Philosophy E-Books Online, Collection 2019, ISBN: 9789004390898., 2020)
Idealist Alternatives to Materialist Philosophies of Science (ed. Philip MacEwen) makes the case that there are other, and arguably better, ways of understanding science than materialism. Philosophical idealism leads the list of challengers but critical realism and various forms of pluralism are fully articulated as well. To ensure that the incumbent is adequately represented, the volume includes a major defence of materialism/naturalism from Anaxagoras to the present. Contributors include Leslie Armour, John D. Norton, and Fred Wilson with a Foreword by Nicholas Rescher. For anyone interested in whether materialism has a monopoly on science, this volume presents a good case for materialism but a better one for its alternatives.